Evaluating VERT as a radiotherapy plan evaluation tool: comparison with treatment planning software. Issue 3 (25th September 2020) - Bridge, P.; Kirby, M. C.; Callender, J. A.
Abstract: Introduction: The virtual environment for radiotherapy training (VERT) helps students to gain technical skills and understanding of 3D anatomy and dosimetry. It has potential as a tool for treatment plan evaluation, although little formal evidence currently supports this. Aim: This paper reports findings from a plan evaluation workshop that facilitated comparison of VERT plan evaluation tools with those provided by conventional treatment planning software (TPS). Method: Students on a pre-registration Post-Graduate Diploma in Radiotherapy worked in small groups evaluating lung plans using both VERT and Eclipse TPS tools. All students were invited to provide ratings concerning how helpful each modality was for a range of evaluation parameters and preferences for use. Results: Most students (11 out of 14) found the session useful and expressed a desire to use VERT in future plan evaluation. The TPS was perceived to be more helpful with constraint-based evaluation while VERT was more helpful with evaluating plans for clinical set-up and delivery ( p < 0·001). Conclusion: Student therapeutic radiographers found VERT to be helpful as a plan evaluation tool alongside standard TPS tools, in particular for clinical set-up and delivery aspects of planning. Future work is ongoing to identify the specific impact of VERT as a plan evaluation tool for both students and qualified planners.